The Basics of Line Balancing and JIT Kitting - Townsend, Beverly (Productivity Press, 2017)
Accessible to the Lean novice and shop floor employee, The Basics of Line Balancing and JIT Kitting explores line balancing and the pre-assembly of components into a finished product in a just-in-time fashion (JIT Kitting). It explains how to use time studies, develop yamazumi charts, discover and eliminate waste, balance your line, and create new.